IMPACT OF PLACENTAL MALARIA ON MATERNAL, AND FETAL CORD RESPONSES AND ITS ROLE IN PREGNANCY IN HADEJIA GENERAL HOSPITAL, JIGAWA STATE - Muhammad, Kabir; James, Orpin; Alhassan, Alhaji Bulama (FUDMA Journal of Sciences, 2026)
Placental malaria remains a significant public health problem in malaria-endemic regions, posing serious risks to pregnant women and their newborns. This study investigated the prevalence, associated risk factors, and immunological impact of PM among pregnant women attending Hadejia General Hospital in Jigawa State, Nigeria. A hospital-based cross-sectional study was conducted among 356 participants. Maternal and Foetal cord samples were collected and examined for malaria parasitaemia using microscopy. Cytokine levels (IL-4, IL-6, IL-10, IL-17A, and IFN-γ) were measured using ELISA. Data were analyzed using SPSS version 20.0. The prevalence of placental malaria was 30.1%. Placental Malaria was significantly associated with younger maternal age (15-35 years), low educational attainment, primigravidity, rural residence, non-use of insecticide-treated nets (ITNs), and fewer than four antenatal care (ANC) visits. Use of ITNs and adequate ANC attendance were identified as protective factors. Cytokine analysis revealed that IL-4 and IL-10 levels in both maternal and fetal cord blood among malaria-positive women, indicating a predominant anti-inflammatory immune response. In contrast, IL-6 and IFN-γ levels were significantly reduced, suggesting suppression of pro-inflammatory responses, while IL-17A showed no significant difference. Correlation analysis demonstrated that IL-4 and IL-10 were positively associated with placental malaria and low birth weight, whereas IL-6 was inversely associated with malaria infection and linked to improved birth outcomes. These findings highlight the need to strengthen malaria prevention strategies during pregnancy through improved ANC coverage, increased ITN use, and targeted health education. The observed immune response patterns also suggest the potential role of cytokines as biomarkers for...